Enhancing Financial Reporting Capacity for Community Waste Banks: An International Collaborative Community Engagement Program in Makassar, Indonesia - Lince Bulutobing; Ts. Shafinar Binti Ismail; Muhammad Khaedar Sahib; Mukminatim; Abd. Muhaemin Nabir; Muryani Arsal (Masterpiece, 2025)
This community engagement program aims to strengthen the financial management capacity of community-based waste banks in Makassar City, Indonesia, through a structured training and mentoring initiative. Waste banks have emerged as an innovative approach to waste management by promoting community participation in waste sorting, recycling, and circular economic practices. However, many waste bank units continue to face significant challenges in preparing accurate and accountable financial reports due to limited knowledge of basic accounting, inconsistent record-keeping, and minimal use of digital tools. This program, implemented collaboratively by Universitas Teknologi MARA (UiTM) Malaysia and several universities in South Sulawesi under the International Association of Economic and Business, focuses on improving the competencies of waste bank managers in preparing simple financial statements aligned with fundamental accounting principles. The activities include needs assessment, training on cash flow records, balance sheets, and income statements, hands-on mentoring, and the introduction of basic digital accounting tools. The program also strengthens institutional accountability and enhances stakeholder trust, contributing to better financial governance within the waste bank ecosystem. Furthermore, the initiative supports the strategic goals of Makassar City in promoting community-based waste management and aligns with the Sustainable Development Goals (SDGs), particularly Goals 11, 12, and 17. The outcomes demonstrate increased financial literacy, improved reporting accuracy, and stronger collaboration between local communities, government institutions, and international academic partners. This program is expected to serve as a replicable model for community empowerment and sustainable environmental management.